A randomized controlled trial evaluating the effects of transversus abdominis plane block with compound lidocaine hydrochloride injection on postoperative pain and opioid consumption and gastrointestinal motility in patients undergoing gynecological laparotomy - Zhang, Linlin; Jia, Zhen; Gao, Tianyu; Wang, Yigang; Zhao, Yuying; Li, Jing; Yu, Yonghao; Li, Qing; Wang, Guolin (Frontiers in Molecular Neuroscience, 2023)
Introduction Incorporation of transversus abdominis plane (TAP) block into multimodal analgesia has been emphasized in Enhanced Recovery protocols (ERPs). However, benefit is limited in clinical practice. A potential explanation is the short duration of analgesia of standard local anesthetics. Herein, this randomized, double-blind, controlled trial evaluated whether TAPB with long-acting compound lidocaine hydrochloride injection reduces postoperative pain. Methods 164 patients undergoing elective gynecological laparotomy under sevoflurane anesthesia randomly received ultrasound-guided TAP block with either saline, or ropivacaine, or compound lidocaine before anesthesia induction. The postoperative pain intensity (primary outcome) was evaluated by pain 11-point numerical rating scale. We also recorded sufentanil consumptions, time to first flatus, side-effects and hospital stay after surgery. Results We reported that pain scores at rest at postoperative 3h in group 0.375% ropivacaine was lower than that in group saline [mean 2.4 (SD 1.2) vs. 3.0 (1.0), p = 0.036]. Compared with saline, 0.4% and 0.6% compound lidocaine caused lower pain scores at rest at postoperative 12h [2.8 (0.9) vs. 2.1 (0.9) and 2.0 (0.9), p = 0.016 and p = 0.006]. Sufentanil usage for the first postoperative 48h was lower in group 0.6% compound lidocaine than group saline [24.2 (5.4) vs. 45.6 (7.5) µg, p < 0.001]. Time to first flatus and hospital stay after surgery was shortest and the incidence of postoperative nausea was lowest in patients receiving 0.6% compound lidocaine. Conclusion TAP block with 0.6% compound lidocaine hydrochloride injection attenuates postoperative pain, reduces opioid consumption, accelerates gastrointestinal function recovery, and shortens length of hospital stay in patients after gynecological laparotomy. Trial registration ClinicalTrials.gov, identifier: NCT04938882.